SIMILARITIES AND DIFFERENCES OF VERB STRUCTURAL CLASSES IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - MUSTAFAEVA NARGIZA (TADQIQOTLAR.UZ, 2024)
This paper provides a comparative analysis of the verb structural classes in English and Uzbek, two languages with distinct linguistic origins and typological features. The study examines the similarities and differences in the morphological, syntactic, and semantic properties of verb structures in these languages. In English, verbs are classified into main verb classes such as transitive, intransitive, copular, and phrasal verbs. These classes are primarily determined by the verb's argument structure and its ability to take direct objects. In contrast, the Uzbek verbal system demonstrates a more complex and nuanced classification, with verbs organized into categories based on transitivity, valency, aspectual properties, and morphological markers.The analysis reveals that while both languages have certain parallel verb structures, such as transitive and intransitive verbs, Uzbek exhibits a richer and more intricate system of verb classes. This includes distinct categories for causative, reflexive, reciprocal, and dative verbs, among others, which are marked through specific morphological processes. The findings of this study contribute to the understanding of cross-linguistic variations in verbal systems and provide insights into the underlying grammatical principles and typological differences between English and Uzbek. The implications of this research extend to areas such as language teaching, translation studies, and theoretical linguistics.